Monitoring VPD (Vapor Pressure Deficit) pada Greenhouse dengan Ventilasi Alamiah - Apriyatama, Muhammad Ivanka; Tusi, Ahmad; Rahmawati, Winda; Suhandy, Diding (Jurnal Agricultural Biosystem Engineering, 2025)
Greenhouses with natural ventilation face challenges in maintaining a stable microclimate, particularly in managing air temperature and humidity, which affect the Vapor Pressure Deficit (VPD). This study aimed to monitor and analyze VPD levels inside a naturally ventilated greenhouse using misting (fogging) treatments at different heights, in order to determine the most effective strategy for VPD control. The research was conducted at the Department of Agricultural Engineering, University of Lampung, using three treatments: no fogging (T1F0), fogging at 50 cm (T2F50), and fogging at 100 cm (T3F100) above the plant canopy. Temperature and humidity data were collected using DHT22 sensors and a hygrometer, and used to calculate VPD values. The results showed that the 50 cm fogging treatment (T2F50) effectively reduced VPD to an average of 0.97 kPa, which is within the optimal range (0.5–1.2 kPa) for plant growth. In contrast, the no-fogging treatment produced the highest VPD value (2.17 kPa), which could cause plant stress. Statistical analysis (ANOVA and LSD test) indicated that fogging height significantly influenced VPD values, especially under hot weather conditions. Therefore, fogging at 50 cm is recommended as the most effective treatment for maintaining optimal VPD in naturally ventilated greenhouses.